Quality Characteristics and Phenolic Compounds of European Pear Cultivars - Öztürk, A.; Demirsoy, L.; Demirsoy, H.; Ozturk, S. (African Ethnomedicines Network editor@africanethnomedicines.net, 2015)
Background: Pear fruits are an important source of plant secondary metabolites and one of the major sources of dietary phenolic compounds. Materials and Methods: The aim of this study was to determine the individual phenolic compounds and some quality characteristics of the flesh and peel of the fruit in four pear cultivars. The phenolic composition of these pear cultivars was determined by high performance liquid chromatography with diode array detection (HPLC-DAD). Results: The fruit flesh firmness ranged from 35.2 to 85.8 N in the pear cultivars. The soluble solids content was higher in the flesh, while titrate-able acidity, vitamin C, individual phenolic compounds and total phenolics were generally higher in the peel. Arbutin, chlorogenic acid and epicatechin were detected as major phenolic compounds in the peel and flesh of pear fruits. Arbutin, chlorogenic acid and epicatechin of the flesh and peel ranged from 834.8 to 937.9 mg kg-1; from 332.1 to 460.7 mg kg-1; and from 77.2 to 104.0 mg kg-1 for ‘Seckel’ pear fruits, respectively. The highest total phenolics were found to be in the peel and flesh of the ‘Flemish Beauty’ pear fruits. Conclusion: Because of the higher level of antioxidant components in the peel of pear fruits (all phenolic compounds and vitamin C) consumption of unpeeled pears, after proper washing, is recommended to maximize the dietary benefit. © 2015, African Ethnomedicines Network. All rights reserved.
Keywords: Arbutin; Chlorogenic Acid; Flesh and Peel; HPLC; Pear Cultivars; Vitamin C